Radiation dose reduction in the setting of cryoballoon ablation for atrial fibrillation. (19th May 2022) - Velagic, V; Prepolec, I; Pasara, V; Percin, L; Posavec, J; Bogdanic, J; Nekic, A; Pezo-Nikolic, B; Puljevic, M; Puljevic, D; Milicic, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cryoballoon (CB) isolation of pulmonary veins (PVI) has become the standard of care for patients suffering from atrial fibrillation (AF). PVI could be achieved by radiofrequency ablation with 3D mapping technology omitting the use of fluoroscopy, so called "0 fluoro" approach. However, CB still requires radiation use. Minimization of radiation exposure is important both for patients and operators. Purpose: We aimed to demonstrate the feasibility of radiation dose reduction in the setting of CB ablation for AF. Methods: We have performed a retrospective study on patients that have undergone CB ablation since the beginning of the AF ablation program in our institution. Procedures were performed under conscious sedation. Both femoral veins were punctured and a single introducer was placed in each vein. A single transseptal puncture was performed guided by intracardiac ultrasound and a 28 mm cryoballoon was used. A single 180 seconds freeze strategy was employed. We analyzed 3 groups of 50 consecutive patients. First group (G1) consisted of subjects at the beginning of our AF program in 2015. In that time, we systematically used 3D rotation angiography for left atrium imaging and higher frame rates both for fluoro (4-10 frames per second - (fps)) and cine (7.5-10 fps) modes of diascopy. Second group (G2) consisted of 50 consecutive patients in 2018 when we stopped using rotational angiography and lowered frame rates (fluoro 4-6 fps, cine 4-6 fps). The third group (G3) consisted of the last 50 patients that we performed in 2021 when we stopped using grid for X ray scatter reduction, lowered fluoroscopy to 2-3 fps, and almost completely abandoned the use of cine mode. Results: We have analyzed in total 150 patients (73% male, 59.4±12.6 years old), 50 in each group. There was a significant decrease of procedure and fluoroscopy time that could be attributed to growing operators' experience and abandoning the use of 3D rotational angiography. More importantly, there was a major decrease in radiation doses applied during the course of the study. Recently, we are using only 2% of radiation doses applied in the beginning of our study (Table). Conclusion: By following a few relatively simple steps (omitting the preprocedural imaging, removing grid from the X ray detector and using very low frame rates) CB ablation could be performed with ultralow radiation exposure. However, a certain level of experience is required to be able to perform CB ablation with relatively low X ray image quality and without preprocedural imaging of left atrium.